Leda and the swan - Caritj, Anna (Riverhead Books, 2021)
"It's Halloween, Saturday night, on a pastoral East coast college campus. Scantily-costumed students ride the fine line between adolescence and adulthood as they prepare for a night of debauchery. Alcohol is flowing. Sex is in the air. Expectations are high as Leda flirts with her thrilling new crush, Ian, and he flirts back. But by the end of the night things will have taken a turn. When Leda later wakes up in Ian's room, she is unsure exactly what happened between them. Meanwhile, the young woman that Leda last spoke to upon leaving the party is now missing. As the campus rouses itself to respond to Charlotte's disappearance, rumors swirl, suspicious facts pile up, and Leda's obsession with her missing classmate grows. Is it just a coincidence that Leda's slightly scary new boyfriend and the missing woman used to be a couple? Is Leda herself in danger? Or only in danger of falling in love? How are you supposed to tell the difference, anyway, if you're a twenty-year-old alone in the world and have never felt any of this before? As Leda becomes more and more dangerously consumed with the mystery of Charlotte and questions about Ian, her motivations begin to blur. Is Leda looking for Charlotte, or trying to find herself?"--